" The impact of strengthening the culture of combating administrative corruption for sustainable development and the elimination of unemployment "From the point of view of students" Taif University Branch of Rania - Qabbani, Abdul Halim Mohammed Ahmed; Musa, Jafar Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The administrative and financial corruption is a global phenomenon and a serious disease that suffers from both the developed and the late world countries. It has negative effects on development and society. It impedes the official work systems, the spread of disguised unemployment and the loss of decision-making. Governments make efforts to eliminate it. The problem of research is that administrative and financial corruption hinders economic and social development, increases unemployment among young people and other groups, wastes resources and weakens both society and the State. The importance of this study lies in the knowledge of the manifestations and forms of administrative corruption and the methods of eliminating it and the study whose importance stems from the importance of the subject which it deals with in general, and from the points dealt with in the study in particular. The aim of this study is to identify the effect of strengthening the culture of administrative corruption for sustainable development and eliminating unemployment from the point of view of students (Taif University, Rania Branch). A sample of the students was investigated and the study reached the results of the most important administrative corruption hinders development and increases the severity of unemployment and made recommendations, most important of which is the need to spread the culture of anti-corruption and control methods to eliminate it.